A Rational Basis Analysis of Terminating Prosecution in Corruption Cases Involving Minimal State Financial Losses - Mantri, Bagus Hanindiyo; Hartiwiningsih, Hartiwiningsih; Rustamaji, Muhammad (International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2025)
The average expenditure incurred by law enforcement agencies in handling corruption cases is approximately IDR 200,000,000. Consequently, pursuing corruption cases involving state financial losses below this threshold proves inefficient. This study aims to analyze and evaluate the urgency of discontinuing the prosecution of corruption offenses that involve relatively minor financial losses to the state. Furthermore, it proposes a framework for reconstructing the legal basis for terminating such prosecutions. This research adopts a doctrinal legal approach, incorporating case-based and conceptual methodologies. The findings reveal that the rationale for ceasing the prosecution of corruption cases involving minimal state losses is grounded in considerations of inefficiency and the absence of explicit legal provisions. The continuation of such prosecutions starkly contrasts the principles of the Economic Analysis of Law approach. In this context, the Attorney General's Office should regulate the prosecution of minor corruption cases using the dominus litis principle. It would involve establishing legal provisions that authorize public prosecutors to exercise discretion in discontinuing prosecutions where the financial harm to the state is minimal, thereby promoting legal clarity and administrative efficiency.